Estudio de la cadena agro productiva del cultivo de cacao y su incidencia en la productividad para proponer un modelo de gestión a los productores cacaoteros, de la parroquia Naranjal del cantón Naranjal de la provincia del Guayas, año 2018 - Sandoval Romero, Ricardo (2019)
The research carried out on the study of the productive Agro Chain of the cultivation of cocoa and its impact on productivity to propose a management model to cocoa producers in the Naranjal Parish of the Naranjal Canton of the Province of Guayas, since the main problem it is the low productivity that cocoa producers have, due to the inefficient management model that has been carried out over the years in the area and that results in low productivity of their crops which has limited the economic development of the producers; The objective of the study is to improve productivity under a management model and in this way the cocoa farmer in the sector can have greater profitability in their crops and this model covers aspects ranging from field production, sales, their crops, the organization which affects productivity, for the research we used the inductive, deductive, analytical methods, besides the types of research we have the field, documentary, descriptive, explanatory, historical, the universe are the 400 producers of cocoa of the Naranjal parish, to whom a survey was applied to know their productive situation, associative, commercialization, finances and their problems in production. In the investigation it was possible to determine that the producers are not legally grouped, their lands are not legalized, the marketing is done in an informal way and several intermediaries without any agreement in terms of quality, quantity and prices , to this is added the imminent phytosanitary problems resulting from a disorderly application of technological packages which affects the productivity of their plantations and consequently their economic income.